Engraving by Borofsky of a Beethoven bust - Borofsky, F. (engraver):::Creator::::::::::::; Kramer, J. (artist):::Contributor::::::::::::; Dietrich, Anton, 1799-1872 (sculptor):::Contributor::::::::::::
Bust of Beethoven, engraving based on the classical sculpture by Dietrich